Integrated Rehabilitation and Nursing Management of Cervical Radiculopathy: A Multidisciplinary Perspective - Hakami, Abdulrahman Mohammed; Alotaibi, Saleh Mohammed; Farsi,DinaHamzaM; Alamri, Bader Mahmoud; Alhazmi, Raheem Mohammed A; Barkat , Reed Abdullah Abdu; Almutairi, Amani Mazyad; Alotaibi, Turki Ghazi Turki; Alqahtani, Norah Mesfer; Saadi, Huda Daifallah Al; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> Cervical radiculopathy is a common condition caused by compression or inflammation of a cervical nerve root, leading to radicular pain, sensory disturbances, and motor weakness in the upper limb. It represents a significant source of disability and work absenteeism, with its etiology shifting from acute disc herniation in younger adults to spondylotic foraminal stenosis in older populations. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> This article aims to provide a comprehensive, multidisciplinary overview of the diagnosis, management, and rehabilitation of cervical radiculopathy, synthesizing perspectives from medicine, nursing, and physical therapy to guide evidence-based, patient-centered care. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> The approach is a synthesis of current clinical guidelines and literature. It details standardized diagnostic procedures, including clinical history, physical examination (e.g., Spurling’s test), and confirmatory imaging (MRI) and electrodiagnostic studies. Management strategies are reviewed, encompassing conservative care (pharmacotherapy, physical therapy, injections) and surgical interventions (anterior discectomy and fusion, posterior foraminotomy). <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> The majority of patients with cervical radiculopathy experience favorable outcomes with conservative management, with many achieving functional recovery within months. For those with refractory symptoms or progressive neurologic deficits, surgical decompression provides more rapid pain relief and functional improvement. Effective outcomes depend on a coordinated, interprofessional approach that integrates accurate diagnosis, staged therapeutic interventions, and structured rehabilitation. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> Successful management of cervical radiculopathy hinges on a multidisciplinary model that prioritizes non-operative care initially and reserves surgery for specific indications. A team-based strategy, combining medical treatment, skilled nursing, and targeted rehabilitation, is essential for optimizing patient recovery, function, and long-term quality of life.